1993
DOI: 10.1159/000182713
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Small Doses of Iodine on Thyroid Function during Caloric Restriction in Normal Subjects

Abstract: It is well recognized that starvation and malnutrition are associated with a low-T3 syndrome in man. A similar condition has been observed after intake of a low carbohydrate hypocaloric diet. However, little is known about the influence of iodine on these conditions. Therefore, we evaluated the effect of iodine supplementation on thyroid function before and after a short-term intake of a low carbohydrate diet in normal subjects residing in an iodine-deficient area. The study was performed in 16 young euthyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…We screened 2019 titles and abstracts after the electronic and bibliographic searches. Twenty-one studies fulfilled the inclusion criteria and reported on UI, thyroglobulin, thyroxine, triiodothyronine, and/or TSH (16,17,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Thirty-seven potential studies were excluded (for reasons, see Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…We screened 2019 titles and abstracts after the electronic and bibliographic searches. Twenty-one studies fulfilled the inclusion criteria and reported on UI, thyroglobulin, thyroxine, triiodothyronine, and/or TSH (16,17,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Thirty-seven potential studies were excluded (for reasons, see Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Reinhardt et al [24] could demon strate in the dietary-induced low T3 syndrome that the severity of NTI was more pronounced in those people who had a higher dietary iodine intake. In the present study, those patients exposed to high doses of iodine pre operatively had slightly higher TSH concentrations but demonstrated the same time pattern with the lowest TSH value on day 1 after surgery.…”
Section: Influence O F Iodine Contamination On Thyroid Functionmentioning
confidence: 99%
“…The low-T3 syndrome is frequently observed during caloric restriction, after surgery and after myocardial infarction. 16,18 On the other hand, an increase in reverse-T3 (rT3), generated by the inner-ring deodination of thyroxine, is observed. rT3 has no thyromimetic activity.…”
mentioning
confidence: 99%